Hazelnut and its by-products: A comprehensive review of nutrition, phytochemical profile, extraction, bioactivities and applications. (1st July 2023) - Zhao, Jiarui; Wang, Xinhe; Lin, He; Lin, Zhe
Highlights: Nutrients and chemicals of hazelnut and its by-products are systematized. The extraction methods of different phytochemicals are reviewed. Hazelnut and its by-products, extracts or components present biological activities. Hazelnut and its by-products are promising in the field of food and medicine. Abstract: As output of hazelnut increases worldwide, so does the amount of by-products, leading to huge waste and environmental stress. This paper focuses on the varieties of hazelnut that have been studied more in the past two decades, and summarizes the research status of hazelnut and its by-products from the aspects of nutritional value, phytochemicals, extraction methods, biological functions and applications. Hazelnut and its by-products are rich in a variety of bioactive constituents, mainly polyphenols, which have antioxidant, antibacterial and prebiotic effects. Moreover, hazelnut shells, husks, and leaves contain taxanes such as paclitaxel, which can inhibit the proliferation of cancer cells. They are potentially good natural sources of paclitaxel compared to the slower growing yew. Therefore, it is essential to further integrate the extraction techniques and health-promoting properties of these nutrients and bioactive substances to expand their application and enhance their value.